Impact of Cylinder Deactivation on Active Diesel Particulate Filter Regeneration at Highway Cruise Conditions - Lu, Xueting; Ding, Chuan; Ramesh, Aswin K.; Shaver, Gregory M.; Holloway, Eric; McCarthy, James; Ruth, Michael; Koeberlein, Edward; Nielsen, Douglas (Frontiers in Mechanical Engineering, 2015)
Abstract—Heavy-duty over-the-road trucks require periodic active diesel particulate filter regeneration to clean the filter of stored particulate matter. These events require sustained temperatures between 500 and 600□C to complete the regeneration process. Engine operation during typical 65 mile/hour highway cruise conditions (1200 rpm/7.6 bar) results in temperatures of approximately 350□C, and can reach approximately 420□C with late fuel injection. This necessitates hydrocarbon fueling of a diesel oxidation catalyst or burner located upstream of the diesel particulate filter to reach the required regeneration temperatures. These strategies require increased fuel consumption, and the presence of a fuel-dosed oxidation catalyst (or burner) between the engine and particulate filter. This paper experimentally demonstrates that, at the highway cruise condition, deactivation of valve motions and fuel injection for two or three (of six) cylinders can instead be used to reach engine outlet temperatures of 520-570□C, a 170-220□C increase compared to normal operation. This is primarily a result of a reduction in the air-to-fuel ratio realized by reducing the displaced cylinder volume through cylinder deactivation.